Men haunted and defined by the past in The Shining and Long Day’s Journey into Night - Santos, Diego Moraes Malachias Silva (Em Tese, 2019)
Despite apparent differences, there are several parallels in the treatment of tradition and masculinity in Eugene O’Neill’s Long Day’s Journey into Night and Stephen King’s The Shining. In this article I suggest comparative approaches between those two works, which, in their core, narrate a man’s flawed attempt at reinstituting a traditional form of masculinity by revisiting and being revisited by the past. Their depiction of masculinities indicates a similar criticism of American traditional manhood and suggests that Stephen King, especially in his earlier novels, combined Naturalistic and Gothic approaches to help redesign modern horror, bringing it to the heart of American culture.